P023 Secondary membranous nephropathy in a patient with a background of rheumatoid arthritis treated with biosimilar etanercept. (26th April 2021) - Sammut, Luke; Leach, Tim; Yalakki, Leena
Abstract: Background/Aims There is a growing number of reports of the development of autoimmune processes related to TNF-targeted therapies. This relationship is much more established with the originator biologics as they have been in clinical use for longer, but data for biosimilar safety is still emerging. Here we describe a case of an 80-year-old gentleman with a background of rheumatoid arthritis who developed membranous nephropathy secondary to Benepali ® . Methods An 80-year-old Caucasian gentleman with a background of seropositive rheumatoid arthritis, diagnosed at the age of 35 years, was maintained in a clinical remission on oral methotrexate 15 mg weekly, until 2017, when his disease started to flare. At that time, his treatment was switched to sulfasalazine, but due to ongoing high disease activity, this was changed again in December 2018 to methotrexate with Benepali ® . His rheumatoid arthritis was controlled with these disease-modifying anti-rheumatic drugs (DMARDs) and his blood test monitoring including full blood count, liver and renal profile (eGFR 80 ml/min/1.73m 2 ) remained normal during the first seven months of treatment. In June 2019, his eGFR deteriorated to 46 and methotrexate was held. Despite this, his eGFR continued to worsen to 28 in July. At that point his Benepali® was discontinued and he was referred to the renal physicians. Results He was normotensive (blood pressure 120/68) and had no dependent oedema. A renal tract ultrasound scan showed normal appearing (with a couple of simple cysts) 10.7/9.4 cm kidneys. Urine dipstick showed 2+ blood and 2+ protein, urine protein:creatinine ratio was 138 mg/mmol (normal ≤ 23) and serum albumin 31 g/L (normal ≥ 34). Serum electrophoresis, HIV and Hepatitis PCRs and serum anti-phospholipase A2 receptor antibody were negative. Renal biopsy confirmed stage I to II membranous nephropathy with mild focal segmental glomerulosclerosis. Reassuringly his renal function and proteinuria continued to improve off Benepali® and both returned to normal a few months after stopping this agent. Conclusion This is the case of an 80-year-old gentleman who developed membranous nephropathy eight months after commencing etanercept biosimilar - Benepali® - for rheumatoid arthritis. Although attribution to a single agent is challenging, we believe that it is likely Benepali® was the main attributing factor for the development of membranous nephropathy. The temporal relationship between the initiation of Benepali® and the subsequent development of biopsy proven membranous nephropathy along with the resolution following withdrawal of Benepali® supports drug-related renal injury. Although TNF inhibitor-induced renal injury is uncommon, this case highlights the need for physicians to maintain a high level of suspicion if a patient on a TNF inhibitor, including biosimilars, develops proteinuria and renal injury. Disclosure L. Sammut: None. T. Leach: None. L. Yalakki: None.